Conscience objection in clinical practice - Montero Vega, Adela; González Araya, Electra (Acta Bioethica, 2011)
Conscience objection is described in clinical practice as a professional right, based mainly in freedom of conscience. A bibliographical review of last ten years is carried out to know the real meaning, extent and transcendence. The conclusion is that it must raise in specific situations, as an exception, with prudence, harmonizing the rights of all participating, reaching equilibrium in decision making, allowing that a society where persons with different values and beliefs live together aspire overall to common good, necessary condition to strengthen democracy.